Hambatan Pembentukan Peraturan Daerah Usul Inisiatif Dewan Perwakilan Rakyat Daerah di Kabupaten Langkat 2015-2019 - Irham Irham (Jurnal Ilmiah Wahana Pendidikan, 2022)
During one period from 2015 to 2019, the Local Government (Pemerintah Daerah or Pemda) with the local Representative (DPRD) of the Langkat Regency formed 49 Local Regulations (Peraturan Daerah or Perda). In the process of drafting the Perda, there were more Local Government-initiated Local Regulation Draft (Rancangan Peraturan Daerah or Ranperda). In terms of the number of Perda that have been approved or passed, it can also be seen that in the process of drafting the Perda for Langkat Regency, the number of proposals for executive initiatives or proposals from the local government is much more than the number of proposals for initiatives from the DPRD that have been approved. The results of the research conducted indicate that the rejection and delay of the evaluation of the Ranperda by the Provincial Government or the Central Government is not the only problem that hinders the formation of the Langkat Regency DPRD Initiative Perda. Barriers to the formation of the DPRD Initiative Local Regulation are also caused by the limited budget for the formation of the Local Regulation, the competence of the Langkat Regency DPRD members, and the political power between DPRD members and the Local Government. The position of the Regent who also doubles as the Chairman of the Party Local Representative of the Political Party that won the election, made the relationship between members of the DPRD and the Local Government of the Regency caused a clientalism relation in the making of Local Regulations. By using William Dunn's policy formulation approach and clientalism relations formed between policy actors, this study will define the factors that become obstacles in the preparation from 2015 to 2019 Langkat Regency legislative initiative draft.